The Impact of DNA Methylation on IL6 mRNA Levels in Hematinic Deficiency and Atopy-Associated Recurrent Aphthous Stomatitis Patients - Nanan Nur’aeny; Dida Akhmad Gurnida; Oki Suwarsa; Irna Sufiawati (International Journal of Dentistry)
Objective. To investigate the DNA methylation using pyrosequencing and its effects on the upregulation of IL6 mRNA in patients with recurrent aphthous stomatitis (RAS) in connection with hematinic deficiency and atopy. Material and Methods. This cross-sectional study was conducted at Dr. Hasan Sadikin Hospital, Bandung, from January–March 2019 and was approved by the Health Research Ethics Committee of Universitas Padjadjaran (Ethics No. 990/UN6.KEP/EC/2018). Furthermore, the subjects had RAS ulcers with a history of at least twice a year along with atopy and dietary imbalance with no history of recurrent intraoral herpes or any systemic diseases. This study was performed on 23 RAS patients and 21 healthy subjects, and the sampling was carried out consecutively. The blood samples were collected from all the subjects, and then, the DNA and RNA were extracted from the peripheral blood mononuclear cells (PBMCs). Consequently, the bisulfite-modified DNA was used to confirm the methylation status of the IL6 gene promoter through the pyrosequencing method. The methylation levels of the IL6 promoter were assessed by a reverse transcriptase-polymerase chain reaction technique. The gene expression of RAS and the control group was analyzed by the 2−ΔΔCT method. The statistical analysis using the Mann–Whitney U test was conducted to evaluate IL6 mRNA levels and DNA methylation with p value <0.05 considered to be statistically significant. Result. The IL6 mRNA levels were approximately 1.88-fold in RAS patients, and there was a significant relationship between the expression of the IL6 gene and the increased risk of RAS p<0.001. It was reported that four out of six sites in the cytosine phosphate guanine (CpG) island IL6 promoter had a lower degree of methylation, and two other sites in patients with RAS had greater methylation compared with control, but not statistically significant. Conclusion. This study showed the upregulation of IL6 mRNA levels in RAS patients compared to control. DNA methylation in the present study is at sites 566–658, whereas the location of the IL6 promoter is at sites 1–1684. Thus, it would be necessary conducting some research at other CpG sites of IL6 promoter islands to determine the status of DNA methylation.